A Human Immunodeficiency Virus Controller With a Large Population of CD4+CD8+ Double-Positive T Cells. (20th March 2015) - Durand, Christine M.; Buckheit, Robert W.; Salgado, Maria; Pohlmeyer, Christopher W.; Walker-Sperling, Victoria E.; Hegarty, Robert W.; Ambinder, Richard F.; Blankson, Joel N.
Abstract: Human immunodeficiency virus (HIV) controllers are patients who control viral replication without antiretroviral therapy. We present the case of an HIV controller who had CD4 and CD8 coexpressed on 40% of his T cells. Although a recent study found that double-positive T cells had superior antiviral capacity in HIV-1 controllers, in this case, the CD4 + CD8 + T cells did not have strong antiviral activity.